Analisis Analisis Neraca Air di Pulau Jawa-Bali sebagai Upaya Antisipasi Krisis Air: Water Balance Analysis at Java-Bali Island for Anticipating Water Crisis - Nurul Chairunnisa; Chusnul Arif; Perdinan; Arif Wibowo (Jurnal Teknik Sipil dan Lingkungan, 2021)
Water is one of the basic necessities used by living things on this earth. Along with the population growth with climate change, there are several cases of water crisis in Java and Bali, especially in the dry season. The purpose of this research is to project water demand and availability based on climate change scenarios, develop an analysis model for the impact of climate change on the water sector based on the water balance, and calculate environmental economic losses resulting from water deficit losses. The type of scenario used in climate analysis is RCP (Representative Carbon Pathway) 4.5 with two types of models. Provinces experiencing very critical water conditions in the 2021-2050 period using the CSIRO model are DKI Jakarta, East Java and Bali, with water criticality indexes of 296.25%, 113.88% and 123.64%, with a water deficit loss of IDR 1.2 billion, IDR 7.93 billion and IDR 0.87 billion. Whereas with the MIROC model, the areas that have very critical water conditions are DKI Jakarta Province with a water criticality index of 220.36%, with a water deficit loss of IDR 0.42 billion.